Design and evaluation of 3D-printed Sr-HT-Gahnite bioceramic for FDA regulatory submission: A Good Laboratory Practice sheep study. (15th January 2023) - Newsom, Ellen T.; Sadeghpour, Ameneh; Entezari, Ali; Vinzons, Joan Lace U.; Stanford, Ralph E.; Mirkhalaf, Mohammad; Chon, Daniel; Dunstan, Colin R.; Zreiqat, Hala
Abstract: There is an unmet clinical need for a spinal fusion implant material that recapitulates the biological and mechanical performance of natural bone. We have developed a bioceramic, Sr-HT-Gahnite, which has been identified as a potential fusion device material. This material has the capacity to transform the future of the global interbody devices market, with follow on social, economic, and environmental benefits, rooted in its remarkable combination of mechanical properties and bioactivity. In this study, and in line with FDA requirements, the in vivo preclinical systemic biological safety of a Sr-HT-Gahnite interbody fusion device is assessed over 26 weeks in sheep under good laboratory practice (GLP). Following the in-life phase, animals are assessed for systemic biological effects via blood haematology and clinical biochemistry, strontium dosage analysis in the blood and wool, and histopathology examination of the distant organs including adrenals, brain, heart, kidneys, liver, lungs and bronchi, skeletal muscle, spinal nerves close to the implanted sites, ovaries, and draining lymph nodes. Our results show that no major changes in blood haematology or biochemistry parameters are observed, no systemic distribution of strontium to the blood and wool, and no macroscopic or histopathological abnormalities in the distant organs when Sr-HT-Gahnite was implanted, compared to baseline and control values. Together, these results indicate the systemic safety of the Sr-HT-Gahnite interbody fusion device. The results of this study extend to the systemic safety of other Sr-HT-Gahnite implanted medical devices in contact with bone or tissue, of similar size and manufactured using the described processes. Statement of significance: This paper is considered original and innovative as it is the first that thoroughly reports the systemic biological safety of previously undescribed bioceramic material, Sr-HT-Gahnite. The study has been performed under good laboratory practice, in line with FDA requirements for assessment of a new interbody fusion device, making the results broadly applicable to the translation of sheep models to the human cervical spine; and also the translation of Sr-HT-Gahnite as a biomaterial for use in additional applications. We expect this study to be of broad interest to the readership of Acta Biomaterilia. Its findings are directly applicable to researchers and clinicians working in bone repair and the development of synthetic biomaterials. Graphical abstract: Image, graphical abstract